The Effect of Yoga Intervention on Reducing Anxiety Levels in Pregnant Women: A Literature Review - Yeni Septia Ningsi; Nur Hidayatul Ainiyah (Jurnal Keperawatan Olahraga, 2025)
Background: Pregnancy is a period of significant physiological and psychological adaptation in a woman's life. In addition to hormonal and physical changes, many pregnant women experience emotional fluctuations, including increased levels of anxiety. Objective: This study aims to evaluate the effect of yoga on anxiety levels in pregnant women based on findings from previous studies. Methods: This literature review was conducted in July 2025. The literature search was performed using four major electronic databases: Scopus (33 articles), PubMed (9 articles), and Google Scholar (10 articles). The keywords used were "yoga" AND "pregnant" AND "anxiety". Eligible articles were determined based on predefined inclusion and exclusion criteria. Results: Of the six articles analyzed, all demonstrated that yoga interventions in pregnant women significantly reduced anxiety levels compared to pre-intervention levels. Discussion: Yoga interventions in pregnant women have been proven effective in reducing anxiety. However, further research is needed to determine the optimal duration and structure of yoga practice for pregnant women to achieve the most effective reduction in anxiety. Conclusion: Yoga operates through complementary physiological and psychological pathways. When practiced regularly and in a structured manner, it can enhance maternal emotional well-being and reduce anxiety during pregnancy and childbirth.